Fluid Bolus Over 15–20 Versus 5–10 Minutes Each in the First Hour of Resuscitation in Children With Septic Shock: A Randomized Controlled Trial*. Issue 10 (October 2017) - Sankar, Jhuma; Ismail, Javed; Sankar, M. Jeeva; C.P., Suresh; Meena, Rameshwar S.
Abstract : Objectives: To compare the effect of administration of 40–60 mL/kg of fluids as fluid boluses in aliquots of 20 mL/kg each over 15–20 minutes with that over 5–10 minutes each on the composite outcome of need for mechanical ventilation and/or impaired oxygenation—increase in oxygenation index by 5 from baseline in the initial 6 and 24 hours in children with septic shock. Design: Randomized controlled trial. Setting: Pediatric emergency and ICU of a tertiary care institute. Patients: Children (< 18 yr old) with septic shock. Interventions: We randomly assigned participants to 15–20 minutes bolus (study group) or 5–10 minutes bolus groups (control group). Measurements and Main Results: We assessed the composite outcomes in the initial 6 and 24 hours after fluid resuscitation in both groups. We performed logistic regression to evaluate factors associated with need for ventilation in the first hour. Data were analyzed using Stata 11.5. Of the 96 children, 45 were randomly assigned to "15–20 minutes group" and 51 to "5–10 minutes group." Key baseline characteristics were not different between the groups. When compared with 5–10 minutes group, fewer children in 15–20 minutes group needed mechanical ventilation or had an increase in oxygenation index in the first 6 hours (36% vs 57%; relative risk, 0.62; 95% CI, 0.39–0.99) and 24 hours (43% vs 68%; relative risk, 0.63; 95% CI, 0.42–0.93) after fluid resuscitation. We did not find any difference in secondary outcomes such as death (1.2; 0.70–2.03), length of stay (mean difference: 0.52; –1.72 to 2.7), or resolution of shock (0.98; 0.63–1.53). Conclusion: Children receiving fluid boluses over 5–10 minutes each had a higher risk of intubation than those receiving boluses over 15–20 minutes each. Notwithstanding the lack of difference in risk of mortality and the possibility that a lower threshold of intubation and mechanical ventilation was used in the presence of fluid overload, our results raise concerns on the current recommendation of administering boluses over 5–10 minutes each in children with septic shock. Abstract : Supplemental Digital Content is available in the text.